Manusia di Muka Cermin Ibn Arabi: Memahami Hakikat Manusia dengan Kacamata Ibn Arabi - Ahmad Kholil (UIN Maulana Malik Ibrahim Malang, 2006)
Although the essence of human being has been questioned long times ago, there are many conceptual answers toward that question. Thus it is common if human beings, as social and individual creatures may try to question it to find new answers. The answer is mainly obtained by contemplating one's self based on the existing concept or reflecting one's self using an individual spiritual experience. The understanding to the essence of human beings described in this writing is based on the concept given by al-Syaikh al-Akbar ibn Arabi who is philosophical as well as sufistic. Who is a man? A man is